The Propeptides of Human Protein C, Factor VII, and Factor IX Are Exchangeable with Regard to Directing Gamma-Carboxylation of these Proteins - Geng, Jie-Ping; Castellino, Francis J (Thrombosis and Haemostasis, 1996)
The specificity of the propeptide sequence in directing vitamin Independent post-translational γ-carboxylation has been assessed by examination of the extent of processing of chimeric constructs of blood coagulation factor VII (fVII), factor IX (fIX) and protein C (PC). One chimera consisted of a protein in which the γ-carboxyglutamic acid (Gla)/helical stack domain of PC (amino acid residues 1 to 46) was replaced by that of fIX (residues 1 to 47) in an otherwise intact PC. Another consisted of the same construction of a fVII/PC Gla domain-based mutant protein. The final chimera contained the leader/propeptide sequence of PC (residues -42 to -1) replaced by that of fIX (residues -46 to -1). In each case, all Glu-precursor Gla residues in the Gla domains of the proteins were fully processed to Gla. These results demonstrate that the propeptides of fIX and PC are capable of directing γ-carboxylation of the Gla regions of either protein, that the propeptide of PC can fully function in γ-carboxylation of the Gla region of fVII, and further suggest that, with regard to γ-carboxylation, communications between the propeptides and Gla domains in intact proteins are general in nature.